PERCEPTIONS AND PREFERENCES OF USER TO THE THERMAL COMFORT IN MENTENG PARK AND HONDA TEBET PARK - . Mariski; Nizar Nasrullah; Andi Gunawan (Jurnal Lanskap Indonesia, 2017)
Green open spaces have a purpose and a great benefit for the balance, continuity, health, comfort, sustainability, and improving the quality of urban environment. Air temperature increases occurred in areas experiencing decline in green open spaces. Among the parameters that contribute to human comfort outdoors, thermal comfort is the most important and significant in determining the quality of outdoor space. The study focuses on analyze the perceptions and preferences of user to the thermal comfort as a quality indicator of park. Methods  used are Chi-Square to analyze perception-preference of user to the site. The Chi-Square was showed that user education were the most influence factor to describe their appreciation to the site in Menteng Park (30.43%). The job background was related with 8% of the perception user in Honda Tebet Park. The category of settled place was influence of 24.14% of the preference user in Menteng Park and 17.24% in Honda Tebet Park.